Planning of an Organisational and Post Structure for the Bureau of the Woordeboek van die Afrikaanse Taal (WAT) - van Schalkwyk, D.J.; Mey, M.T. (Lexikos, 1992)
Resulting from financial pressure and the desire to accelerate the completion of lexicographical projects, planning and management aspects are receiving increasing attention by lexicographical institutions. However, these important matters are not adequately emphasized at lexicographical conferences. The topic of this article is the planning and management of a lexicographical project, especially the planning of its organisational and post structure. Although it here concerns the planning and management of the Bureau of the WAT, the views expressed can also be applied to other lexicographical projects. The designing of an organisational and post structure of any institution is closely related to its strategic planning. The decision to adjust the organisational and post structure of the Bureau of the WAT logically resulted from its strategic planning which was done during 1989. For the Bureau to give meaning to its endeavour and to perform its task the organisational and post structure should meet the following requirements: (i) Work processes, support systems and work ethics should focus on end results; (ii) The editorial process should be accelerated with the aid of technology and editorial methodology; (iii) Contextual relevance of the content of the WAT should be guaranteed; (iv) The management culture should be user-driven; and (v) A business management approach which supports cost sensitivity and which focuses on generation of income. This article discusses the organisational and post structure which has been designed for the Bureau of the WAT with these requirements in mind. Because this article focuses on planners and managers of lexicographical projects and not in the first place on planning and management specialists, some ideas and standard details are being looked at more closely. Keywords: strategic planning, organisational and post structure, group plan, line function, staff supporting service, critical performance area, critical performance output, success indicators, control information, organisational analysis, job evaluation, remuneration structure, remuneration package, organisational diagram, job descriptions, organisational analysis statement, key functions, performance management system, lexicographical projects